INNOVATION IN TEACHING ENGLISH FOR LAW ENFORCEMENT: A TECHNOLOGY-INTEGRATED APPROACH - Pielmus, Cristina Georgeta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Nowadays, innovation is seen as a process of change, whose implementation is supposed to bring about more effectiveness in those organizations that envision such reformative initiatives. In language education, innovation is often related to the emergence and experimentation of both pedagogical and technology-integrated approaches to teaching and learning. The technology-based language teaching refers to the integration of modern technology into the language class, either as a tool or as a resource. From this perspective, the article starts with an overview of the literature regarding key-concepts we operate with throughout the paper and is organized in several subsections attempting first to define what innovation in language education is, then to clarify what English for Law Enforcement is against the distinction between English for Specific Purposes as opposed to General English. Further the paper focuses on the use of ICT in English language teaching, enumerating and illustrating how the technology-based approaches can be employed in language classes. This section makes the shift to the next one, which discusses a concrete case of teaching English for Law Enforcement students in Romania, exemplifying the “what” and “how” of the use of technology in such a language learning environment, pointing out both its benefits and drawbacks for both teachers and learners.